Social Media as a Space for Democracy: A Narrative Review of Digital Activism in Southeast Asia - Vanie, Adevy (Yayasan Sinergi Kawula Muda, 2025)
Digital activism has become a defining feature of civic engagement in Southeast Asia, where social media platforms function as both spaces of empowerment and instruments of control. This narrative review aims to analyze how digital activism shapes political discourse, identity formation, and collective action in the region. Literature was systematically retrieved from databases including Scopus, PubMed, and Google Scholar, using Boolean strategies and thematic keywords such as digital activism, civic engagement, social media, and Southeast Asia. Inclusion criteria focused on peer-reviewed studies offering empirical insights, while exclusion criteria eliminated works lacking data or regional specificity. The findings reveal that youth and marginalized groups use social media to construct civic identities, mobilize protests, and amplify their voices globally. Political consumerism, symbolic online practices such as hashtags and memes, and transnational solidarity campaigns illustrate the innovative forms of digital engagement emerging in the region. However, challenges remain significant. Disinformation campaigns, censorship, surveillance, and structural inequalities restrict inclusivity and diminish the sustainability of digital activism. Comparative perspectives suggest that while Southeast Asia shares similarities with global trends, its unique socio-political context amplifies both opportunities and risks. Policy frameworks are crucial in shaping outcomes, with transparent governance, independent regulation, and digital literacy initiatives identified as key enablers of sustainable civic participation. The review concludes that digital activism represents both promise and peril, requiring context-sensitive policies and future research to address limitations and expand understanding. Key challenges include disinformation, censorship, and structural inequalities that demand targeted policy responses.